2012
DOI: 10.1161/atvbaha.111.237065
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Development of Abdominal Aortic Aneurysm by Glycolysis Restriction

Abstract: Objective-The mechanisms underlying abdominal aortic aneurysm development remain unknown. We hypothesized that acceleration of glucose metabolism with the upregulation of glucose transporters is associated with abdominal aortic aneurysm development. Methods and Results-Enhanced accumulation of the modified glucose analogue 18 fluoro-deoxyglucose by positron emission tomography imaging in the human abdominal aortic aneurysm was associated with protein expressions of glucose transporters-1 and -3, assessed by We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…Although the expression of mitochondrial proteins has not previously been investigated in human AAA, an enhanced glycolytic activity and ROS production in the aortic wall has been suggested to contribute to the pathogenesis of aneurysm development [16,17,18]. Glycolysis is a metabolic process restricted to the cytosol of the cell.Our finding that PGC1α, TFAM and VDAC expression was reduced in AAA supports the hypothesis that reduced mitochondrial activity is involved in the pathogenesis of AAA.…”
Section: Discussionmentioning
confidence: 99%
“…Although the expression of mitochondrial proteins has not previously been investigated in human AAA, an enhanced glycolytic activity and ROS production in the aortic wall has been suggested to contribute to the pathogenesis of aneurysm development [16,17,18]. Glycolysis is a metabolic process restricted to the cytosol of the cell.Our finding that PGC1α, TFAM and VDAC expression was reduced in AAA supports the hypothesis that reduced mitochondrial activity is involved in the pathogenesis of AAA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Bock et al demonstrated that glycolysis is a major source of ATP in ECs. The glycolysis activity of ECs is closely related to cell function, such as proliferation [9], migration [9,23] and adherence [24]. Lactate is the final product of glycolysis and regulates glycolysis and intracellular pH.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in time courses of ARF and BSO and variability in detection of the C 62 that the observed effects may not be limited to the Trx system. The longer time frame for BSO treatment could allow changes because of transcriptional activation as shown previously by Harris et al (27).…”
Section: Insulin Regulation Of Translation Lipid Metabolism and Cellmentioning
confidence: 95%
“…This could be important in conditions of energy limitation, such as can occur during development and tissue repair (61,62), where oxidation could impair development or tissue repair and recovery. Conversely, enhanced dependence on glycolytic energy metabolism occurs in cancer, a characteristic previously developed as a therapeutic approach for cancer treatment (63).…”
Section: Insulin Regulation Of Translation Lipid Metabolism and Cellmentioning
confidence: 99%